Impulsive differential equations - Samoilenko, A. M. (World Scientific, 1995)
For researchers in nonlinear science, this work includes coverage of linear systems, stability of solutions, periodic and almost periodic impulsive systems, integral sets of impulsive systems, optimal control in impulsive systems, and more